2018
DOI: 10.3982/qe557
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence and the employment experience of older workers

Abstract: This paper provides new interpretations of the effects of rising economic turbulence—an increase in the rate of skill depreciation upon job loss—and its interaction with labor market institutions. We have three main results, based on a life‐cycle model with labor market frictions and labor force participation decisions. First, rising economic turbulence during the 1970s and 1980s accounts for the decline in employment among older workers in the United States. Second, the interaction between turbulence and inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Overall, it is not clear the extent to which scarring or loss of skill due to long unemployment spells might have significantly affected long-term trends in participation. Krueger et al (2014) and Lalé (2018) are the closest studies we found to aiming to quantify the potential magnitude of the contribution of this type of long-term effects on the overall recent evolution of the LFPR. Although these effects were longer lasting than the duration of the recession, we also would expect them to be temporary, as the negative effects dissipate when cohorts affected by the recession exit the working ages.…”
Section: Long-term Impacts Of Unemployment Spellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it is not clear the extent to which scarring or loss of skill due to long unemployment spells might have significantly affected long-term trends in participation. Krueger et al (2014) and Lalé (2018) are the closest studies we found to aiming to quantify the potential magnitude of the contribution of this type of long-term effects on the overall recent evolution of the LFPR. Although these effects were longer lasting than the duration of the recession, we also would expect them to be temporary, as the negative effects dissipate when cohorts affected by the recession exit the working ages.…”
Section: Long-term Impacts Of Unemployment Spellsmentioning
confidence: 99%
“…This causes variations in the rates of skill loss among workers and may be particularly damaging for older workers because skill accumulation is a time‐consuming process. Lalé (2018) calibrates a general equilibrium life‐cycle model with labor market frictions to account for the impact of the interaction between economic turbulence and institutions on men's LFP. In this setting, the secular decline in LFPR of older male workers (ages 55–64) is consistent with an increase in economic turbulence, given the institutional setting.…”
Section: Factors That Affect Labor Force Participation Decisionmentioning
confidence: 99%
“…Aggregate employment differences across countries are largely driven by the two ends of the age spectrum: while prime-age employment rates are broadly similar, unemployment among younger workers and labor force participation rates of older individuals differ wildly across countries (see Cohen et al [1997], OECD [2006], Chéron et al [2009], Lalé [2018]). These facts are well known and highly influential when it comes to formulating policy proposals in order to improve aggregate employment performances.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies typically abstract from labor force participation. Lalé [2018] develops a similar model but allows for decisions along the participation margin. His focus, however, is on only one end of the age spectrum (older workers).…”
Section: Introductionmentioning
confidence: 99%
“…Lalé [2018] makes similar assumptions (viz. stochastic shocks to workers' preferences over leisure) in a model with an operative participation margin that produces worker flows in and out of the labor force.8 Prescott et al[2009], andChang et al [2019] rely on a non-convex mapping from hours to labor services in order to distinguish the extensive and intensive margins of labor supply.…”
mentioning
confidence: 99%